The Public Interest Acquisition of Land for Development - Hutama, Arya Rizky (ann4publisher@gmail.com, 2025)
Background. Soil is essential to all human life on Earth, and the existence of land is an inseparable component of human existence. Development is vital to enhancing human quality of life, and the demand for land as a capital asset is increasing in tandem with development activities. Aims. The government urgently needs land for the planned project site to catalyze development for both itself and the commercial sector. Methods. Normative studies focus on the analysis of legal principles, statutes, and regulations, particularly those related to research and the legal challenges that arise in this context. Data sources are identified through a literature review, employing both primary and secondary data derived from research projects and reviews. Primary data was obtained by analyzing laws, regulations, and documents related to land purchase. Result. Land acquisition for public interest aims to acquire land for developmental projects that promote the welfare and prosperity. Land acquisition must be conducted in accordance with the principles of the 1945 Constitution and national agrarian laws of the nation, state, and society, while safeguarding the legal rights of rightful proprietors and aligning with national and state values. Conclusion. Therefore, land purchase restrictions satisfy procedural justice requirements. Once the impacted parties have been compensated, the land acquisition is deemed complete